2019
DOI: 10.1111/omi.12259
|View full text |Cite
|
Sign up to set email alerts
|

Induction and inhibition of oral malodor

Abstract: Volatile sulfur compounds (VSCs) such as hydrogen sulfide (H2S) and methyl mercaptan (CH3SH) are the main components of oral malodor, and are produced as the end products of the proteolytic processes of oral microorganisms. The main pathway of proteolysis is the metabolism of sulfur‐containing amino acids by gram‐negative anaerobic bacteria. Gram‐positive bacteria may promote VSC production by gram‐negative anaerobes by cleaving sugar chains from glycoproteins and thus providing proteins. A large variety of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 105 publications
(143 reference statements)
0
49
0
3
Order By: Relevance
“…The VSCs are the most essential substances responsible for malodor. They are products of metabolism of sulfur amino acids: methionine, cysteine, and homocysteine in the Gram-negative anaerobic bacteria [25,30,47,60]. Hydrogen sulfide and mercaptans are the principal end products [38].…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…The VSCs are the most essential substances responsible for malodor. They are products of metabolism of sulfur amino acids: methionine, cysteine, and homocysteine in the Gram-negative anaerobic bacteria [25,30,47,60]. Hydrogen sulfide and mercaptans are the principal end products [38].…”
Section: Volatile Compoundsmentioning
confidence: 99%
“…There is disagreement as to whether H. pylori is present in the oral cavity. The bacterial communities in the oral cavity are highly complex and include a large number of VSC-producing bacteria [2]. The oral malodor associated with H. pylori is unlikely to be caused by its production of VSCs but, rather, by exacerbation of periodontitis and changes in the populations of some oral bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, Marshall et al [1] first reported oral malodor in subjects experimentally infected with H. pylori; however, the malodor was judged subjectively. Upper gastrointestinal disorders can cause oral malodor, but oral malodor is linked to the oral cavity in 90% of cases [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by various volatile molecules including volatile sulfur compounds (VSCs), aromatic compounds, amines, and so on . Especially, VSCs, mainly including H 2 S, CH 3 SH, and CH 3 SCH 3 , are considered as the major components associated with halitosis , which accounts for about 90% of total halitosis . Besides, it has been reported that mostly (85%) of the pathology causing halitosis originated from the oral cavity , which has become a common phenomenon affecting the quality of social life .…”
Section: Introductionmentioning
confidence: 99%